Challenges and progress in the understanding and modelling of the wheel–rail creep forces. Issue 7 (3rd July 2021) - Vollebregt, Edwin; Six, Klaus; Polach, Oldrich
Abstract : This paper surveys advances in the understanding and modelling of wheel–rail creep forces. The main focus is placed on tribological aspects, for which significant progress was made in the past two decades. We emphasise the role played by the surface conditions, i.e. the presence of liquid and solid layers, surface roughness, and near-surface plastic deformation. As these surface conditions may change over time, transient changes may be obtained in the creep force characteristic. This brings feedback into the picture, with consequences and opportunities for optimised adhesion recovery, traction control, and braking systems.